Dimethylethanolamine Decreases Epileptiform Activity in Acute Human Hippocampal Slices in vitro - Kraus, Larissa; Hetsch, Florian; Schneider, Ulf C.; Radbruch, Helena; Holtkamp, Martin; Meier, Jochen C.; Fidzinski, Pawel (Frontiers in Molecular Neuroscience, 2019)
Temporal lobe epilepsy (TLE) is the most common form of focal epilepsy with about 30% of patients developing pharmacoresistance. These patients continue to suffer from seizures despite polytherapy with antiepileptic drugs and have an increased risk for premature death, thus presenting an incentive for development of new antiepileptic therapies. The aim of our study was to identify and test the antiepileptic efficacy of a new substance using human brain ex vivo. We decided to investigate dimethylethanolamine (DMEA), which has been tested as treatment in various neurological diseases, albeit the functional mechanism of action was never fully understood. In more detail, we investigated effects of DMEA on epileptic activity in CA1 pyramidal cell layer of human hippocampal tissue in vitro. Burst activity was induced by elevated K+ and 4-aminopyridine. We were able to show antiepileptic effects of DMEA in resected hippocampal tissue from TLE patients. DMEA decreased epileptic activity in the majority of samples with variable effect strength. In conclusion, DMEA might present a new approach for treatment in pharmacoresistant TLE. Further studies will be required to identify the antiepileptic mechanism of action of DMEA and its molecular targets.